Adjuvant systemic therapy in melanoma: Relative versus absolute benefit; the number needed to treat (NNT) versus the number needed to harm (NNH)? - Alexander C.J. van Akkooi; Mario Mandala; Paul Nathan; Andrew Haydon; Michael Postow; Piotr Rutkowski (EJC Skin Cancer)
Adjuvant (ADJ) systemic therapy has transformed melanoma treatment during the past decade. There are, however, still important unanswered questions that lead to debates on the utility and place of ADJ therapy for melanoma. When ADJ trials are reported, they present a hazard ratio with a significant P-value. This illustrates the relative benefit of the ADJ therapy, but do not give insight into the absolute benefit for an individual patient. Number needed to treat (NNT) expresses the number of patients required to receive an intervention in order to prevent one event of interest. It is measured by taking the reciprocal of absolute risk reduction. The smaller is the NNT, the greater the effectiveness of the intervention in the study population. NNT is not static, it can change over time, but will not improve until infinity, it will plateau at some point. NNT needs to be balanced with the number needed to harm (NNH) caused by an ADJ therapy, that, by definition, is overtreatment for patient populations. Other aspects that we, as society, must consider regarding ADJ therapies is if there is only a benefit in preventing recurrences or if this translates into an overall survival benefit. On the other hand, living without stage IV disease is of obvious benefit to the quality of life of patients, as well as the costs of treatment are more severe once they have progressed to stage IV disease. Conclusion: We must weigh the absolute benefits of adjuvant systemic therapy in melanoma as a number needed to treat (NNT) and have agreement within society of what is an acceptable balance of NNT versus NNH. There is an urgent need to develop a bespoke, personalized panel of biomarkers to better predict prognosis of individual patients and subsequently have a better identification of who actually benefits from adjuvant systemic therapy and thereby reducing the NNT.